Histórias afro-argentinas - Lima, Henrique Espada (Afro-Ásia, 2024)
Resenha de: ALBERTO, Paulina L. Black Legend. The Many Lives of Raúl Grigera and the Power of Racial Storytelling in Argentina, Cambridge (Mas.): Cambridge University Press, 2022. 410 p.